1998
DOI: 10.1080/15216549800201552
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of protein kinase C‐α detected in human colorectal cancer

Abstract: The down‐regulation of protein kinase C (PKC) was examined by Western blot procedure on about 30 tissue samples derived from human colorectal cancer and the corresponding normal mucosa. PKC‐α down‐regulation was detected in 60% of the cancer tissues compared with the respective normal mucosa and was observed in a higher frequency with the tissues under more advanced cancer stages. However, the frequencies of the down‐regulation of PKC‐δ and PKC‐ζ were lower than that of PKC‐α. These results suggest that a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
6
15
0
Order By: Relevance
“…Our data about up-regulation of PKCi/k in Apc Min/+ tumors are not confirmed by Paoni and Leclerc (whereas PKCL/E was not tested by Klein et al), but they support results obtained from patients and other animal models (21). For PKCf, the previous studies (with the exception of Leclerc) agree with us on a down-regulation of this gene in tumor tissue, which again is consistent with patient data (40) and other animal models (37).…”
Section: Pkcasupporting
confidence: 82%
“…Our data about up-regulation of PKCi/k in Apc Min/+ tumors are not confirmed by Paoni and Leclerc (whereas PKCL/E was not tested by Klein et al), but they support results obtained from patients and other animal models (21). For PKCf, the previous studies (with the exception of Leclerc) agree with us on a down-regulation of this gene in tumor tissue, which again is consistent with patient data (40) and other animal models (37).…”
Section: Pkcasupporting
confidence: 82%
“…Consistent with this supposition, the down-regulation of PKC-ct was observed in human colorectal cancer in our laboratory (16). Based on the previous results (l, 8), the molecular mechanism of PKC down-regulation seems to be composed of at least two processes, namely the binding of PKC to plasma membrane and the subsequent formation of an activated conformation on the membrane, and proteolytic degradation of PKC by some endogenous protease.…”
Section: Modulation By Diacylglycerol Of Pkc-ct Binding To Plasma Memsupporting
confidence: 74%
“…Overexpression of PKCßII in colonic epithelium seems to results in hyperproliferation and an increased susceptibility to carcinogenesis with an early increase in carcinogenesis, whereas PKC was downregulated in colonic tumors (43,44). Data from Orchel et al (45) have shown that differentiation of Caco-2 cells by butyrate treatment is dependent on PKC and c-Jun N-terminal kinase (JNK) activity.…”
Section: Discussionmentioning
confidence: 99%